E-learning software package for introduction of modern radar technology - Tan, Jason Soon Ee (2014)
To let students better understand the module "Introduction to Modern Radar", computational models based on Matlab program are developed. It allows the student to explore and study the radar equation, Doppler Frequency and the phased array radar beam pattern. The following two parts of works are mainly covered in this report: